KONSTRUKSI SOSIAL PEKERJAAN PEMULUNG TPA PAKUSARI KABUPATEN JEMBER (Lembaga Pengembangan Kinerja Dosen, 2023)
This research aims to explore the social construction of scavenger work at the Pakusari Final Disposal Site (TPA), Jember Regency, East Java. This research was conducted using a qualitative approach and data was collected through in-depth interviews with 4 respondents, consisting of scavenger workers, the community and related parties. The research results show that the scavenger profession is considered a lowly and less prestigious job by some people. However, the scavengers at Pakusari TPA view this work as an important source of income and they have special skills in collecting used items that still have value. In addition, scavengers are faced with various challenges, such as unsafe working conditions, limited access to health and education facilities, and negative stigma attached to their profession. However, the scavengers at Pakusari TPA have strategies and mechanisms to overcome negative stigma and build a positive identity as scavengers.